ANALISIS FAKTOR INTERNAL DAN EKSTERNAL PENENTU PEMBIAYAAN MURABAHAH PADA PERBANKAN SYARIAH DI INDONESIA - Rohmah, Nikmatur; Zuhroh, Idah (Program Studi Ekonomi Pembangunan, 2021)
Murabahah financing is the agreement to buy and sell goods between the bank and the customer at the price of the acquisition plus the profit margin agreed by both parties, where the sharia bank buys the goods needed by the customer and then To the customer in question. This research aims to analyse internal and external factors determining the Murabahah financing on Sharia banking in Indonesia. The data used in this study is secondary data of I-IV in the period of 2013-2018, which is sourced from the Financial Services Authority and World Bank official website. Data analysis techniques use a regression analysis of data panels with the help of Statistics software program Eviews9. The results showed that the Capital Adequacy Ratio (CAR), Third Party Fund (DPK), Non Performing Financing (NPF) and inflation simultaneously affected the murabahah financing on Sharia banking in Indonesia with the value of F-count ( 185.5056) > F-table (2.42). The result of T test shows that CAR has no effect on Murabahah financing, then DPK, NPF and inflation partially have a significant positive influence on financing murabahah on sharia banking in Indonesia.